Cardiac tamponade due to ruptured coronary-pulmonary artery fistula aneurysm: a case report. Issue 3 (3rd May 2020) - Hijikata, Sadahiro; Sakurai, Kaoru; Maeba, Satoru; Azegami, Koji
Abstract: Background: Coronary artery fistulas are rare and most commonly asymptomatic; however, they can become enlarged and rupture in some cases. Case summary: We report a case of a 51-year-old woman who was brought to our hospital unconscious in an ambulance. Cardiac tamponade caused by the rupture of an aneurismal coronary-pulmonary artery fistula (CPAF) was detected by contrast-enhanced computed tomography and confirmed by invasive coronary angiography. Due to prompt diagnosis and subsequent surgical intervention, the patient's condition was rapidly improved, and she was discharged from the hospital. Discussion: Coronary-pulmonary artery fistula aneurysm rupture requires rapid diagnosis and treatment, and thus, in cases with cardiac tamponade and coronary aneurysm, CPAF aneurysm rupture should be considered.